Two studies in gas-phase ion spectroscopy vacuum-ultraviolet negative photoion spectroscopy and ion-molecule reaction kinetics - Simpson, Matthew J (Springer Theses, Recognizing Outstanding Ph.D. Research)
In this thesis Matthew Simpson reports two areas of work in gas ion spectroscopy, each investigation in itself worthy of a PhD. The first study uses tunable vacuum-ultraviolet radiation from a synchrotron to identify negative ions from twenty four photoexcited polyatomic molecules in the gas phase. From these experiments, Matthew collects a vast amount of data and summarises and reviews ion-pair formation from polyatomic molecules.  The second study is on selected ion flow tube mass spectrometry. Matthew investigates the reactions of cations and anions with ethene, monofluoroethene, 1,1-difluoroethene and tetrafluoroethene. In this study Matthew tries to explain why certain products are formed preferentially over other products at a microscopic level of understanding. The data recorded in this thesis form the most comprehensive collection of information about anion formation and are the basis of a review and numerous articles in specialist journals. Introduction and background information -- The experiments.-  Vacuum-ultraviolet negative photoion spectroscopy of SF6, CF4 and SF5CF3 -- Vacuum-ultraviolet negative photoion spectroscopy of CF3Cl, CF3Br and CF3I -- Vacuum-ultraviolet negative photoion spectroscopy of SF5Cl -- Vacuum-ultraviolet negative photoion spectroscopy of small polyatomic molecules -- The reactions of CFn+ (n = 1-3) with C2H4, C2H3F, CH2CF2 and C2HF3 -- The reactions of C2F4+ with C2H4, C2H3F, CH2CF2 and C2HF3 -- Reactions of OH-, O-, CF3-, F- and O2- with C2H4, C2H3F, CH2CF2, C2HF3 and C2F4 .